The Strategies Used by The English Teachers in Teaching Vocabulary at Darul Huffadh Islamic Boarding School - Nur, Serliah; Muthiah, Muthiah; Ridwan, Dian Eldyanti (STAIN Majene, 2023)
This research was carried out to investigate the strategies used by the English teachers in teaching vocabulary at Darul Huffadh Islamic Boarding School and to figure out the teachers` perception in applying the strategy in teaching vocabulary. This research was conducted using qualitative method to answer the research questions. The instruments of this research are interviews and observational checklist. The subject of this research was teachers who teach in classes 8a, 8b, 8c, and 8d. The result shows that the teachers used different strategies in teaching vocabulary, namely picture, action and movement, contrast, explanation and translation. In addition, based on the teachers` perception, those strategies were relevant to teach vocabulary to the students because the teachers can mix up more than two strategies in one meeting. Therefore, the teachers taught English using various activities and strategies to make students enjoy learning English. This research is expected to provide the teachers and prospective teachers as well as readers about strategies that are suitable to use in teaching vocabulary. The findings of this research provide some options of teaching strategies that can be considered to be used in other educational institutions